Inspiring Writing in Nursing: A Clinical Nurse Specialist–Led Program. Issue 2 (March 2019) - Ansryan, Lianna Z.; Marshall, Caroline; Aronow, Harriet Udin; Chan, Alice; Coleman, Bernice
Abstract : Background: Hospitals are constantly involved in quality improvement and research projects investing considerable money, time, and effort in supporting these projects; however, there is not always a strong enough focus on publishing the results. The challenge lies in engaging clinicians to publish their work. One of the hallmarks of the clinical nurse specialist is mentoring, and this has led to the creation of our Inspiring Writing in Nursing (IWIN) program. Purpose: The goal of IWIN cohort was to engage and promote publication submissions from frontline clinicians. The 18-member Nursing Research and Evidence-Driven Practice Council (NR-EDPC) supports more than 3000 nurses in quality and research projects. Two senior librarians support our council and staff. In 2014, we launched our first IWIN cohort to mentor nurses in writing and submitting for publication. Evaluation: The NR-EDPC motto "meet them where they are" applies to both location and level of research/EDPC knowledge and skill. An Annual Nursing Research Conference showcases the products of nursing science. The first cohort of IWIN enrolled 11 mentees, and after a yearlong journey, we submitted 5 of 11 manuscripts, 3 withdrew, and 3 are still under revisions. From the 5 submissions, 3 were published, 1 was rejected, and 1 is currently under revision. Discussion: With support and the infrastructure of our NR-EDPC, we are launching our second IWIN cohort.